REM34 and REM35 Control Female and Male Gametophyte Development in Arabidopsis thaliana - Caselli, Francesca; Beretta, Veronica Maria; Mantegazza, Otho; Petrella, Rosanna; Leo, Giulia; Guazzotti, Andrea; Herrera-Ubaldo, Humberto; de Folter, Stefan; Mendes, Marta Adelina; Kater, Martin M.; Gregis, Veronica (Frontiers in Plant Science, 2019)
The REproductive Meristem (REM) gene family encodes for transcription factors belonging to the B3 DNA binding domain superfamily. In Arabidopsis thaliana the REM gene family is composed of 45 members, preferentially expressed during flower, ovule and seed development. Only a few members of this family have been functionally characterized: VERNALIZATION1 (VRN1) and most recently TARGET OF FLC AND SVP1 (TFS1) regulate flowering time and VERDANDI (VDD), together with VALKYRIE (VAL) control the death of the receptive synergid cell in the female gametophyte. We investigated the role of REM34, REM35 and REM36, three closely related and linked genes similarly expressed in both female and male gametophytes. Simultaneous silencing by RNA interference (RNAi) caused about 50% of the ovules to remain unfertilized. Careful evaluation of both ovule and pollen development showed that this partial sterility of the transgenic RNAi lines was due to a post meiotic block in both female and male gametophytes. Furthermore, protein interaction assays revealed that REM34 and REM35 interact, which suggests that they work together during the first stages of gametogenesis.